India's eucalyptus craze : the god that failed. - Saxena, N.C. (New Delhi, 1994)
It is a seminal study on the forest economy of India.... With this, Ecol ogy Economics appears to have arrived in the country. It is to be perused by all those interested in ecological problems which have political economy dimensions.
Keywords: Eucalyptus industry India